Redescription of Austrolebias accorsii (Cyprinodontiformes: Rivulidae) and description of a new species of the genus from the upper Paraguay River basin - Heinz Arno Drawert; Carlos Ergueta (Neotropical Ichthyology, 2024)
Abstract Austrolebias accorsii is redescribed based on specimens from type-locality, nearby temporary pools, and other locations within the same hydrologic unit. Additionally, a novel Austrolebias species is described, exclusively found in two temporary waterbodies in “Abayoy”, a unique vegetation type situated in the transitional zone between the Dry Chaco, Chiquitano Dry Forest, and Pantanal Flooded Savannas ecoregions in southeastern Bolivia, bordering Paraguay, where the last voluntarily isolated indigenous people outside the Amazon in America reside. Diagnostic characters for both species are presented. Within Austrolebias two species groups are recognized with different morphological characters, geographical distribution, and ecological traits of their habitats. Furthermore, we suggest the usage of median and interquartile range rather than mean and standard deviation to analyze morphometric and meristic data of rivulids, given the typically non-Gaussian distribution of this data.